Representasi Makna Pesan Motivasi Pada Lirik Lagu Stay Alive Jeon Jungkook BTS - Chusna, Nailu Roifatul; Hakim, Lukman (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2023)
The topic of Korean Pop or Kpop music is a very interesting discussion, especially among teenagers. Kpop it self has a distinctive style of song lyrics, with a mix of Korean and English, so that everyone can enjoy the song as a whole. The lyrics of the song it self contain a series of words that are produced from the form of meaning, expression or mood, about something that happens in the singer. This study aims to get an idea of ​​what the meaning of the motivational messages contained in the song Stay Alive sung by Jeon Jungkook BTS is. This research uses descriptive qualitative method with semiotic analysis approach of Ferdinand De Saussure. The results of the study show several meanings of motivational messages contained in the song stay alive, namely always love your self, don't forget to always be grateful and fight for anything in life and accept God's destiny with a positive attitude.